Bulk Etch Rate and the Activation Energy of the CR-39 Detector using Thickness Difference Method - Abrar K. Mustafa Al-Ramadhni; Saeed H. Saeed Al-Niaemi (Kirkuk Journal of Science, 2018)
The aim of this paper is to determine the bulk etch rate Vb of the nuclear track detector CR-39 using the method based on measuring the thickness of the layer removed from the surface of the detector (the thickness difference) by the chemical etching, and then studying how to change it with the temperature of the etching solution to extract an empirical relationship between them. The detector samples were etched in a 6 N of NaOH solution at temperatures 80, 70, 60 and 501 oC, and the thickness of the removed layer was determined by successive measuring the detector thickness for etching times of 1-9 h increasing with 1 h intervals. The results showed that the values of Vb range between 2.351-0.605 μm/h for etching temperature 50-80 oC respectively. An exponential relationship was obtained between the bulk etch rate and the etching temperature. It was noted that the results were consistent with that obtained by other studies using the track Length-diameter- (Le-D) measurement method. The slight difference in Vb magnitudes between the compared results is due to the slight difference in the concentration of the etching solution in certain